The Natural History Museum Data Portal. (11th April 2019) - Scott, Ben; Baker, Ed; Woodburn, Matt; Vincent, Sarah; Hardy, Helen; Smith, Vincent S
Abstract: The Natural History Museum, London (NHM), generates and holds some of the largest global data sets relating to the biological and geological diversity of the natural world. A majority of these data were, until 2015, not widely accessible, and, even when published, were typically hard to find, poorly documented and in formats that impede discovery and integration. To better serve the bespoke needs of user communities outside and within the NHM, a dedicated data portal was developed to surface these data sets and provide a sustainable platform to encourage their citation and reuse. This paper describes the technical development of the data portal, from its inception to beta launch in December 2015, its first 2 years of operation, and future plans for the project. It outlines the development principles adopted for this prototypical project, which subsequently informed new digital project management methodologies at the NHM. The process of developing the data portal acted as a driver to implement policies necessary to encourage a culture of data sharing at the NHM.